2018
DOI: 10.1007/s11207-018-1263-z
|View full text |Cite
|
Sign up to set email alerts
|

Harmonics of Solar Radio Spikes at Metric Wavelengths

Abstract: This paper presents the latest observations from the newly-built solar radio spectrograph at the Chashan Solar Observatory. On July 18 2016, the spectrograph records a solar spike burst event, which has several episodes showing harmonic structures, with the second, third, and fourth harmonics. The lower harmonic radio spike emissions are observed later than the higher harmonic bands, and the temporal delay of the second (third) harmonic relative to the fourth harmonic is about 30 -40 (10) ms. Based on the elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The decimetric spike emission in Fig. 31 could also be produced by plasma emission (Zheleznyakov and Zaitsev 1975;Kuijpers et al 1981;Ba ´rta et al 2011a, b;Karlicky ´and Ba ´rta 2011;Feng et al 2018;Karlicky ´et al 2021), the accepted mechanism for solar metric type II and type III bursts as well as for fine structure in Type IV bursts (e.g., Kaneda et al 2017). Marque ´et al (2018) write, ''[The ECM emission] mechanism is usually expected to not operate in the solar corona, because of the high electron plasma frequency.…”
Section: Observations Of Extreme Decimetric Radio Burstsmentioning
confidence: 99%
“…The decimetric spike emission in Fig. 31 could also be produced by plasma emission (Zheleznyakov and Zaitsev 1975;Kuijpers et al 1981;Ba ´rta et al 2011a, b;Karlicky ´and Ba ´rta 2011;Feng et al 2018;Karlicky ´et al 2021), the accepted mechanism for solar metric type II and type III bursts as well as for fine structure in Type IV bursts (e.g., Kaneda et al 2017). Marque ´et al (2018) write, ''[The ECM emission] mechanism is usually expected to not operate in the solar corona, because of the high electron plasma frequency.…”
Section: Observations Of Extreme Decimetric Radio Burstsmentioning
confidence: 99%
“…Radio spectral observations of type III bursts, spike structures associated with type IV bursts and zebra patterns could also provide estimates of the magnetic field in the coronal source regions of the radio emission [21][22][23]. In addition, when the emission mechanisms are known, microwave imaging at one or more frequencies could be used to produce maps of the coronal magnetic field strength in limited regions [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the present status of the field using such data, in the following, we just present two examples of studies on the temporal delay of solar spikes. Using the spectral data (with a temporal resolution of 10 ms and a spectral resolution of 100 kHz) from the Chashan Solar Observatory (CSO) operated by Shandong University, Feng et al [5] found that the time delay between harmonics of solar radio spikes could be as small as the temporal resolution of the data (∼10 ms), while in an earlier study, Bouratzis et al (2016) found that the duration of metric radio spikes is ∼60 ms according to an analysis of 12,000 events [6] (see Chernov et al [7] for more studies on radio fine structures using high-resolution spectral data).…”
Section: Introductionmentioning
confidence: 99%
“…Mingantu Spectral Radioheliograph (MUSER) [9] generates nearly 3.5 TB data per day. Chashan Solar Observatory (CSO) [6] operated by Shandong University obtains up to 300 GB of data per day. This results in a rapid increase of data volume waiting to be classified and analyzed.…”
Section: Introductionmentioning
confidence: 99%